Effect of Carbon Nanotubes on CNT Reinforced FGM Nano Plate under Thermo Mechanical Loading. (2016) - Kumar, Lalit; Harsha, S.P.
Abstract: This study analysis the effect of Carbon Nanotubes (CNT) on CNT reinforced Functionally Graded Materials (FGM) nano plate under mechanical and thermo mechanical loading using finite element analysis. Material properties of the plate are considered to be graded in the thickness direction linearly by varying numbers of CNTs in each layer. FGM plate results are compared with plane Al nano plate and CNT reinforced composite nano plate (same overall percentage of CNT) of same dimension and same boundary conditions. In investigation, it is found that CNT increases significant strength in both FGM and composite. But in mechanical loading, CNT provides more strength in composite compare to FGM, while in thermo mechanical FGM stronger than composite.